Pelembagaan Arisan Menjadi StartupJasa Keuangan Mikro Syariah - Vidyasari, Rahmanita; Masjono, Ali; Supriyadi, Agus; Mirati, R. Elly; Abrianto, Heri (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2025)
It comes from the routine activities of an MSME Nyiur Gading community, a social gathering which is called Arisan. It has been running for 3 years, and all members have felt the benefits of the arisan. It turns out that there are members who are en tangled in illegal online loans (pinjol). Due to the need for fast and relatively large funding but the ability of the arisan to be relatively small, the idea arose to turn the arisan into a business that could help finance its members in the form of sharia microfinance. The main purpose of this activity is to enhance the role and improve the welfare of members, as well as to help free themselves from financial dependence on parties outside the community. The Community Based Participatory Research (CBPR) method is used in this service activity because it is community-based and involves the community members themselves. In the service activity, the material was also given about understanding Islamic finance and Sharia microfinance, as well as financial literacy about personal financial management as a guideline to becoming financially independent. The 30 participants in this activity, who are members of the Nyiur Gading MSMEs, agreed to improve the financial management of social gatherings in a more professional manner and agreed to form a Sharia financial services startup as a source of financing to overcome dependence on parties outside the community. The team provides an application for this Sharia financial services startup, which is based on Ms. Excel, so it is easy to learn. After running for two months with assistance, this Sharia financial startup has helped its members get financing quickly and easily, and the payment process runs smoothly. Providing material on understanding the impor tance of personal financial planning has also been proven to increase participants’ financial literacy from 70% to 91%.